Impact of Fermented or Enzymatically Fermented Dried Olive Pomace on Growth, Expression of Digestive Enzyme and Glucose Transporter Genes, Oxidative Stability of Frozen Meat, and Economic Efficiency of Broiler Chickens - Ibrahim, Doaa; Moustafa, Amira; Shahin, Sara E.; Sherief, Wafaa R. I. A.; Abdallah, Karima; Farag, Mohamed F. M.; Nassan, Mohamed A.; Ibrahim, Seham M. (Frontiers in Veterinary Science, 2021)
Using dried olive pomace as complementary energy sources in poultry feed is still limited due to its low protein and high fiber contents. This study aimed to evaluate the effects of fermented olive pomace (FOP) with or without enzymatic treatment on growth, modulations of genes encoding digestive enzymes and glucose transporters, meat oxidative stability, and economic efficiency of broiler chickens. A total of 1400 day-old, broiler chicks (Ross 308) were randomly allocated in seven dietary treatments with ten replicates of 20 birds/replicate. Treatments included control (basal corn-soybean diet) and other six treatments in which basal diet was replaced by three levels (7.5, 15, and 30%) of FOPI or enzymatically treated FOPII for 42 days. The highest body weight gain was found in groups fed 7.5 and 15% FOPII (increased by 6.6 and 12.5 %, respectively when compared with the control group). Also, feeding on 7.5 and 15% FOPII yielded a better feed conversion ratio and improved the digestibility of crude protein, fat, and crude fiber. The expression of the SGLT-1 gene was upregulated in groups fed FOPI and FOPII when compared with control group. Fat % and cholesterol content inbreast meat were significantly reduced (p<0.05) by nearly 13.7 and 16.7 % in groups fed FOPI and FOPII at the level of 15 and 30%. Total phenolic and flavonoid contents in breast meat were significantly increased in groups fed 15 and 30% FOPI and FOPII when compared with control group and even after a long period of frozen storage. After 180 days of frozen storage, the inclusion of high levels of FOP significantly increased (p<0.05) glutathione peroxide, total superoxide dismutase contents, and meat ability to scavenge free radical 1,1-diphenyl-2-picrylhydrazyl. The results of this study indicated that dietary inclusion of 15 % FOP II could enhance growth performance and economic efficiency of broiler chickens. Moreover, a higher inclusion level of FOPI or FOPII could enhance the quality and increase the oxidative stability of frozen meat and extend storage time.